Pertanian Organik Terpadu di Desa Wukirsari, Sleman, Yogyakarta Sebagai Usaha Pemulihan Kesuburan Lahan Terimbas Erupsi Merapi 2010 dan Pencapaian Desa Mandiri Sejahtera - Dwi Umi Siswanti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Community service activities at Wukirsari village was preceded by many concerns land damaged by the eruption of Merapi 2010. Researchers encourage Wukirsari people to self-sufficient in the provision of liquid organic fertilizer and manure plus. It is intended to restore the soil nutrient that improves soil structure. The target of this activity were increasing the agricultural productivity, cost efficiency of production, improvement of agricultural cultivation, encouraging self-sufficiency of liquid organic fertilizer and manure plus and the establishment of agricultural enterprises. The conclusion of these program are the liquid organic fertilizer producted by Wukirsari farmer response positively to the growth and productivity of rice plants. The barriers of this program was delayed of the establishment of business entities will be overcome with the implementation of the third period (2015) of the community service program which cooperate with the Student Community Service Program (KKN PPM UGM).